ʻAttalak thāng watthanatham Čhangwat Kānčhanaburī (Samnakngān Watthanatham Čhangwat Kānčhanaburī, 2012)
On tradition and culture, beliefs, products, prominent figures, and places that are the cultural identity of Kanchanaburi Province, Central Thailand.